Organizational commitment of collaborators of financial institutions in the Junin region - Paredes-Pérez, Marco A.J. (2021)
Objective. To describe the level of organizational commitment in the “collaborators” of the financial institutions in the Junin region. Methods. The approach was quantitative, basic type, descriptive level and descriptive- cross-sectional design. Observation was applied, as well as inductive-deductive and analytic-synthetic methods. The instrument was the organizational engagement questionnaire of Meyer, Allen and Smith, composed of 21 items. The sample was made up of 210 collaborators. Results. The level of organizational commitment is medium, the level of affective commitment is high, the level of normative commitment is medium and the level of continuity commitment is medium. Conclusions. Respondents' answers fluctuated between the Likert scale values: 2 "disagree", 3 "neither agree nor disagree" and 4 "agree"; therefore, it is considered that there is a medium level of organizational commitment in the “collaborators” of the financial institutions in the Junín region.